The analysis of the "Theory of functions of the complex variable" test with attraction of models Russia and Birnbaum - Lidia A. Muratova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In work the analysis of the "Theory of Functions of a Complex Variable" test is carried out. A main objective - identification of possible shortcomings of dough and definition of ways of their elimination. As material results of the testing held at petrotechnological faculty of SAMGTU served. Research of dough was carried out by means of the modern theory of testing (IRT). Thus two models were used: Russia and two-parametrical model of Birnbaum. After transition to a uniform interval scale of logits the combined histograms of levels of knowledge and difficulty of tasks were constructed. According to model Russia characteristic curve dependences of probability of the correct answers on the level of knowledge at the fixed difficulty are received. For check of compliance of empirical data of model Russia schedules of all tasks of dough are submitted. The differentiating ability of a task was estimated by means of two-parametrical model of Birnbaum. Characteristic curves, the corresponding probabilities of the correct answers depending on the level of knowledge at the fixed difficulty are constructed and taking into account a task diskriminativnost. Information functions of tasks and all dough according to model Russia and two-parametrical model of Birnbaum are found. As a result it appeared that requirements imposed to qualitative dough such, as are fulfilled: the look close to normal for histograms of levels of knowledge and difficulty of tasks, and also a certain type of information functions. Besides more than a half of tasks have admissible values of coefficients of a diskriminativnost. As for other tasks, the carried-out analysis showed what need to be overworked what to remove and what tasks should be added to achieve more uniform distribution them on difficulty. The offered transformations of dough will allow to make it more adapted tool for measurement of knowledge.